Translational research from bioinformatics to animal studies: Exploring gene expression and muscle health in COPD through selenium nanoparticles and exercise - Mahdi Bakhshi; Abdolali Bnaeifar; Sajjad Arshadi; Behzad Bazgir (Journal of Exercise & Organ Cross Talk)
Recent studies highlight the role of molecular pathways, such as oxidative stress response and mitochondrial function, in COPD. This study explores the role of the PGC-1α gene, a key regulator of mitochondrial biogenesis and energy metabolism, using a rat model and bioinformatics analysis of human lung tissue samples. This study utilized a combined approach, analyzing gene expression in rat lung tissue alongside bioinformatics analysis of public human datasets. A total of 42 male Wistar rats were divided into seven groups, receiving treatments including cigarette smoke extract (CSE), nano-selenium (SeNPs), and aerobic interval training (AIT). PGC-1α expression levels were evaluated using quantitative Real-Time PCR (qRT-PCR) and analyzed using one-way ANOVA, followed by Dunnett’s post hoc test for multiple comparisons to determine significance across groups. The CSE+SeNPs+AIT group exhibited significantly higher PGC-1α expression compared to controls (p = 0.0289), indicating a potential protective role of SeNPs and exercise against oxidative stress. Bioinformatics analysis identified 250 differentially expressed genes (DEGs), with PGC-1α emerging as a critical hub gene associated with pathways like oxidative stress response and mitochondrial regulation. Protein-protein interaction (PPI) analysis further highlighted the centrality of PGC-1α in COPD pathophysiology. This study underscores the importance of PGC-1α in regulating mitochondrial function and oxidative stress in COPD. The findings suggest that PGC-1α could serve as a potential therapeutic target, offering insights into the development of interventions aimed at improving respiratory health in COPD patients. Future research should focus on validating these findings in clinical settings and exploring the therapeutic potential of PGC-1α modulation.